PENGARUH MOTIVASI KERJA DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU SD NEGERI DI KECAMATAN TANGGUNGHARJO KABUPATEN GROBOGAN - Rani Setyawati; Noor Miyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine (1) The effect of work motivation on teacher performance, (2) The effect of professional competence on teacher performance, (3) The joint influence between work motivation and professional competence on performance.This research was conducted in public elementary schools in Kec.Tanggungharjo Kab.Grobogan. This research is a sample study, with the sampling technique used is simple random sampling with the intention that each subject has the same opportunity to be sampled. The population of this study were all teachers in public elementary schools in Kec.Tanggungharjo Kab.Grobogan. The subjects analyzed in this study were 52 teachers who were calculated based on the 50% sampling technique. Data collection techniques are using questionnaires, observation and documentation. The data validity test used is validity test and reliability test. Prerequisite test analysis includes normality test, linearity test, multicollinearity test. Hypothesis testing uses simple regression test, which is analyzed by comparing the value of t table with t count and multiple regression test, which is analyzed by comparing F count with F table. The results of this study show: (1) There is a positive and significant effect of work motivation on the performance of public elementary school teachers in Tanggungharjo District as evidenced by the correlation coefficient rcount < rtable (0.533 < 0.279) with a coefficient of determination of 0.284 which means that 28.4% of this variable affects teacher performance and 71.6% is influenced by other variables. (2) There is a positive and significant effect of professional competence on the performance of public elementary school teachers in Tanggungharjo District as evidenced by the correlation coefficient rcount < rtable (0.638 < 0.279) with a coefficient of determination of 0.407 which means that 40.7% of this variable affects teacher performance and 59.3% is influenced by other variables. (3) There is a positive and significant influence between work motivation and professional competence together on teacher performance as evidenced by the correlation coefficient rcount < rtable (0.686 < 0.279) with an effective contribution of 47% which means 53% of teacher performance is influenced by other variables.